Konflik Program Lumbung Pangan: Studi Kasus Desa Pilang di Kabupaten Pulang Pisau, Provinsi Kalimantan Tengah - Krismes Santo Haloho (Sociale : Journal of Social and Political Sciences, 2025)
The Food Estate in Pilang was implemented in 2021 with land extensification rice fields, there was a rejection action by one of the landowners when the contractor carried out land clearing. Method of research is qualitative description with interactive model data analysis using conflict trees and conflict management diagrams. Conclusion research shows that social problems are vertical land conflicts, conflicts occur because landowners refuse contractors to carry out land clearing from the plan map recommended by SID team. Refusal occurred because the land owned by the residents is a forest containing rubber plantations as a source of livelihood. Conflict is destructive because of landowner disappointment caused by ripped clothing while blocking heavy equipment at the program site. Land conflict resolution is carried out by the superordinate with a dominating style by the government and avoidance by the contractor, because conflict is resolved by relocating the land to another area. Impact of conflict on the program was that the planned land area was not realized according to the target area, while for community there were four (4) farmer groups that did not have land, which caused dissatisfaction because condition of printed land is not optimal and jealousy between farmer groups that have been opened with groups that have not been opened. Injustice in the implementation of the program that triggered land conflicts is a form of neglect of the social status of landowners, external constraints addressed by the government and contractors show the low vertical mobility of subordinate groups in Pilang.